2022
DOI: 10.3390/polym14245361
|View full text |Cite
|
Sign up to set email alerts
|

Functionalized Soybean Oil- and Vanillin-Based Dual Cure Photopolymerizable System for Light-Based 3D Structuring

Abstract: A novel dual cure photopolymerizable system was developed by combining two plant-derived acrylic monomers, acrylated epoxidized soybean oil and vanillin dimethacrylate, as well as the thiol monomer pentaerythritol tetrakis (3-mercaptopropionate). Carefully selected resin composition allowed the researchers to overcome earlier stability/premature polymerization problems and to obtain stable (up to six months at 4 °C) and selectively-polymerizable resin. The resin demonstrated rapid photocuring without an induct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…The degree of swelling is directly related to the crosslink density; it can be concluded that the 3D printed samples have a high crosslinking degree. [ 35 ]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The degree of swelling is directly related to the crosslink density; it can be concluded that the 3D printed samples have a high crosslinking degree. [ 35 ]…”
Section: Resultsmentioning
confidence: 99%
“…The degree of swelling is directly related to the crosslink density; it can be concluded that the 3D printed samples have a high crosslinking degree. [35] The DSC performed on the cured sample confirmed the amorphous phase of the resin and allowed for the identification of the glass transition temperature. Indeed no melting or crystallization peaks had been detected; on the other hand a variation of the slope of the signal is clearly visible in Figure 6a, corresponding to the glass transition temperature (T g ) of 15.6 °C.…”
Section: Physical Chemical Thermal and Mechanical Properties Of 3d Pr...mentioning
confidence: 86%
“…However, their swelling values in toluene were lower (1.48–9.14%) indicating that these polymers are not easily soluble in toluene. GDMA- and GTMA-based polymers ( B2 , B3 , B5 and B6 ) showed higher swelling values in toluene than in acetone due to their structure being more similar to the non-polar solvent toluene than to the polar solvent acetone [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…The type of solvent also affected the swelling of the polymers. Polymers showed the higher swelling value in toluene than in acetone because the structure of the synthesized polymers was more similar to that of the nonpolar solvent toluene than to the polar solvent acetone [ 31 ].…”
Section: Resultsmentioning
confidence: 99%